Building a high-resolution chronology for northern Hokkaido – A case study of the Late Holocene Hamanaka 2 site on Rebun Island, Hokkaido (Japan). (April 2021) - Junno, Ari; Dury, Jack P.R.; Leipe, Christian; Wagner, Mayke; Tarasov, Pavel E.; Hirasawa, Yu; Jordan, Peter D.; Kato, Hirofumi
Highlights: Reservoir offsets and lack of materials with terrestrial carbon complicate 14 C-dating. Multi-phase site's chronology was investigated using a Bayesian model and seed dates. This resulted in increased temporal resolution at the study site. These 14 C-data point to a synchrony between cultural shifts and landscape changes. The approach should be useful when 14 C-dating assemblages in maritime environments. Abstract: Archaeological radiocarbon dating in coastal northern Hokkaido is challenged by the marine reservoir effect and the scarcity of materials with terrestrial carbon sources. This has contributed to gaps and general uncertainty in the timing of the region's culture-historical periods. The Late Holocene site of Hamanaka 2 on Rebun Island, featuring a stratified shell midden context with excellent preservation of organic remains, provides an ideal setting for addressing this issue. A Bayesian chronological model was deployed to study the timing of the site using a series of radiocarbon-dated macrobotanical samples. This resulted in narrowed-down estimated age-ranges in eight of thirteen phases examined, providing the site with a more accurate radiocarbon chronology than before. These temporal data were consequently integrated with local palaeoecological evidence, revealing synchrony between cultural chronology and human-induced landscape transformations. The study demonstrates that the technique should permit more efficient building of archaeological chronologies in similar maritime environments.